Analisis Gereja Ortodoks di Asia Timur Tengah dan Relevansinya Bagi Perkembangan Teologi Gereja di Era Modern - Surimawati Laia; Yuslina Halawa; Malik Bambangan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the analysis of the Orthodox church in Middle East Asia and its relevance to the development of church theology in the modern era. The background of this research focuses on the role of the Orthodox church in the social, cultural, and religious context of the Middle East Asian region, as well as its challenges in facing the development of contemporary church theology. The method used in this research is a qualitative approach, with descriptive analysis of the history, doctrines, and religious practices of the Orthodox church, as well as its interaction with the challenges of the modern world. The findings show that the Orthodox churches in the region have a significant contribution to the development of global theology, despite facing various challenges in terms of identity and modernity. Orthodox churches play an important role in maintaining the heritage of traditional theology while responding to the dynamics of changing times. In conclusion, the relevance of Orthodox churches in Middle East Asia is crucial in enriching contemporary theological discourse, both in the context of religious understanding and the application of the principles of faith in the modern world.